Diagnostic value of saline contrast sonohysterography comparing with hysteroscopy for detecting endometrial abnormalities in women with abnormal uterine bleeding - Farzaneh Goharzad; Razieh Dehghani Firouzabadi; Mohammad Ali Karimzadeh (Shahid Sadoughi University of Medical Science, Yazd, Iran, 2011)
Background: Abnormal uterine bleeding is a common presentation of uterine abnormalities among premenopausal and postmenopausal women.Objective: To evaluate and compare the diagnostic accuracy of saline contrast sonohysterography and hysteroscopy for detecting the cause of abnormal uterine bleeding.Materials and Methods: A total of 65 women with abnormal uterine bleeding were enrolled in this study. A prior saline contrast sonohysetrography followed by a hysteroscopy was performed in all cases. Sensitivity, specificity, positive and negative predictive value and test accuracy were calculated.Results: As the most common abnormality, SCSH showed hyperplasia in 19 patients while hysteroscopy diagnosed polyp in 15 cases. A sensitivity of 73.3%, 71.4% and 90.9% were reported for polyp, hyperplasia and submucous myoma respectively whereas the specificity was calculated 96% for polyps, 82.3% for hyperplasia and 90.7% for submucous myoma.Conclusion: Comparing with hysteroscopy, sonohysterography showed a high sensitivity and specificity for detecting submucous myoma but not for endometrial polyp and endometrial hyperplasia